Um enfoque da organização composicional de textos bem formados , segundo a Fuvest - Castelhano, Telma Cristina da Silva Frasca (2016)
This work is related to the research line "Text and Discourse in oral and written forms" of Postgraduate Program in Portuguese Language of PUC-SP. The general objective is to contribute to teachers and students regarding the preparation for taking entrance examinations with results that might provide a guideline on textual production of dissertative texts. The specific objectives are: highlight the text sequences and their encrustation on the textual scheme of the texts that are considered as model by the board that corrects the exams of Fuvest; confront the point of view projected by the reduced text proposed by Fuvest as a starting point for the production of essays by the applicant, with the projection of a new point of view selected by the candidate, having as parameter the understanding of the reduced proposed theme, i.e. the strategy used for the opinionated construction; highlight the theming and expansions by semantic progression of essays considered "well written", i.e. referral. The theoretical foundation is based on Textual Linguistics and, more specifically, in Textual Analysis of Discourses. To achieve our goal, we followed the study of textual sequences of Adam (2011) and the studies of Silveira (2012) on the argumentative text of a thesis and two theses. The results of the analyzes indicate that: the hierarchical explanatory sequence is most frequent in the texts published by Fuvest compared with the argumentative sequence; there is semantic progression by theming through the new point of view selected by the candidate